DAMPAK ALIH FUNGSI LAHAN TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT KECAMATAN BUNGKU TIMUR KABUPATEN MOROWALI - Kamarudin, Lu’lu (Katalogis, 2016)
This research aims to find out the impact of land conversion on social and economic life, in relation to land ownership, type of work, social relationship, and society’s income levels at One Pute Jaya and Bahomoahi villages Bungku Timur district, Morowali regency. This was a qualitative descriptive research. The results showed that (1) Land conversion gives impact on the society’s land ownership. (2) Land conversion does not give impact on the society’s work types. (3) Land conversion gives significant impact on the social relationship among the society. (4) Land conversion gives impact on the income levels of the society, particularly at Bahomoahi and One Pute jaya villages. In other words, the income of the farmers and fishermen’s decline after the land conversion.